A Theoretical Model for Internet Banking: Beyond Perceived Usefulness and Ease of Use - Ezzi, Shaza W (Archives of Business Research, 2014)
As with other types of electronic banking like ATM’s, telephone banking, and electronic funds transfer, Internet banking like has evolved from consumers’ needs to have greater access to banking services beyond most banks teller-staffed, normal operating hours. Additionally, Internet banking has grown rapidly from the recent and dramatic increases in e-commerce. Internet banking (IB) continues to dominate the landscape of electronic banking as consumers continue to use IB to complete routine banking transactions in addition to conducting on-line sales and purchasing. This study presents a theoretical model designed to help researchers and practitioners better understand the acceptance and adoption of Internet Banking. The proposed model may be particularly useful in developing nations where consumers are reluctant to use Internet Banking even when the services are available. However, a review of several studies that have investigated consumers’ acceptance of Internet banking services from a variety of perspectives have not reached a clear consensus of the factors that contribute to overall consumer acceptance and adoption. Following the seminal information systems research of Davis, Bagozzi and Warshaw’s (1989) Technology Acceptance Model, the purpose in this paper is to introduce a theoretical model for understanding the acceptance and adoption of Internet banking services. Following an extensive review of the literature, the proposed Internet Banking Model is specified and introduced. The paper concludes with discussions of the managerial implications and avenues for future research. Keywords: Internet banking, technology acceptance model (TAM), consumer behavior